Karakteristik Kejadian Stunting Pada Anak Usia Sekolah - Fadillah, Annisa Nur; Ramadita, Desta; Kamrullah, Safrullah; Nurjannah, Misbah; Ernawati, Rini (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Chronic malnutrition can cause stunting. Due to the fact that data on child stunting keeps growing every year, stunting is a concern in Indonesia and perhaps even the entire world. This study attempts to examine information regarding the traits of moms and kids who suffer from stunting. A crosssectional quantitative methodology was applied, and 72 respondents with stunting. SPSS is used to tabulate and analyze data. Results study is sex and age of the kids with stunting, the mother's age, profession, and level of education characteristic data. The traits discovered are the primary and secondary causes of stunting.